Medicine for wound healing from the discarded seeds of tamarind - Rahman, Mohammad Tariqur; Mohamad, Mohd Yusuf; Akram, Haris B.; Bero, Dinie Najwa (2010)
Introduction: Tamarind indicus belongs to the subfamily Caesalpinioideae. Seeds from tamarind comprises of testa (20-30%) and kernel (70-75%) are rich in various biochemical components such as protein (131.3 g/kg), oil (48.2 g/kg) and fiber (67.1g/kg). In an effort to make use of tamarind seeds we have studied its possible pharmacological benefits for wound healing. Results: Induced wound (5 mm in diameter) on mouse epidermis were treated topically with various forms of tamarind seed extracts. Depending on the reduction of the size of the wound, it was observed that extracts prepared in PBS (PE) was found at least equally efficient as the commercially available wound healing agent, i.e., Socoseryl (PC). In both these cases, average time requirement for complete wound healing is 10 days (n=7). Other forms of extracts using water (WE), ethanol (EE) and methanol (ME) required an average 11 dyas for compelte healing while the wound left untreated require at least 14 days (n=5-7). Unlike the the synthetic wound healing agent, treatment with the extracts did not result in development of inflammation. Conclusions: Extracts from tamarind seed which is otherwise a waste, can be used as a potential natural source of wound healing which at the same time will be safer than synthetic drugs and will be more economical.